A rational irrationality: Reviewing the Concept of Rationality in Conventional Economics and Islamic Economics - Muhammad Hasyim Ibnu Abbas (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
In analyzing economic phenomena that occur in the midst of society, economists always use assumptions. Rationality is the most important assumption and becomes the main step in analyzing the phenomenon. Individuals in making decisions are assumed to be rational. Problems arise when rational human measurements for the economy of the classical generation are selfish and tend to be selfish. This article discusses how the assumption of rationality is debated among the three major streams of economics today. The three streams referred to are Classical-Neoclassical Economist, Behavioral Economist, and Islamic Economist. Neoclassical-Economist with the assumption that rational individuals are individuals who are concerned with personal desires, Economists of Behavior with the theory of Bounded-Rationality, and Islamic Economists with the argument that the main goal of humans is God.